KAP1 Regulates Gene Networks Controlling T cell Development and Responsiveness - Santoni de Sio, F.R. (FASEB J, 2012)
The modulation of chromatin status at specific genomic loci controls lymphoid differentiation. Here, we investigated the role played in this process by KAP1, the universal cofactor of KRAB-containing zinc finger proteins (KRAB-ZFP), a tetrapod-restricted family of transcriptional repressors. T lymphoid KAP1 knockout mice displayed expansions of specific T cell populations, with impaired responses to stimulation and deregulation of genes involved in cell survival, cytoskeletal rearrangement, and immune signalling. Furthermore, chromatin studies demonstrate that KAP1 directly regulates the expression of a number of these genes, among which Foxo1 seemed of particular interest. Likely at least partly responsible for these effects, a small number of KRAB/ZFPs are selectively expressed in T cells. These results reveal the as-of-yet unsuspected importance of the KRAB/KAP1 epigenetic regulation system for T cell differentiation and function.